COVID-19 and the National Lockdown: How Food Choice and Dietary Habits Changed for Families in the United Kingdom - Scott, L.; Ensaff, H. (Frontiers in Nutrition, 2022)
COVID-19 changed the way families in the UK live, with as yet uncertain impacts to food choice and dietary habits. This study sought to explore food-related experiences and changes to behaviour of families with children, during the pandemic. Semi-structured one-to-one interviews with parents (n=20) and, separately, their children (n=22; aged 8-10 years) were conducted. An inductive thematic approach was adopted for the data analysis, and four main themes emerged: commensality; elevated place of food in the home; snacking; and food shopping. Study findings highlighted several changes: some related to increased snacking and more takeaway food; others were more favourable, including spending more time together, increased home cooking, more efficient shopping practices and reduced food waste. Overall, an elevation of the place of food within the home was apparent, alongside enhanced food literacy, and some evidence of the relocalisation of food. This study contributes to the international literature on the impact of COVID-19 on family lifestyle behaviours, specifically food choice and dietary habits; further research into the longer-term effects of COVID-19 on family food practices is required.